Analisis Pengaruh Penambahan Abu Cangkang Sawit pada HESC untuk Peningkatan Kualitas Mutu Beton - Masrura, Delfian; Rahman, Aulia; Salena, Inseun Yuri; Alvisyahri, Alvisyahri; Putri, Cut Nadia (Universitas Teuku Umar, 2025)
West Aceh Regency produces 2,804 tons/year of palm oil with a total of 1.8 million tons/year of palm shell waste. Utilization and solutions to palm shell waste can be done by burning palm shells at high temperatures until they become ashes. Palm ash contains a certain amount of silica and has pozzolan qualities. This study aims to decide the impact of the utilize of palm shell ash and silicafume in High Early Strength Concrete (HESC) concrete mixtures on the magnitude of the compressive strength of concrete. The method used is the experimental laboratory method using American Concrete Institute (ACI) method. The composition of the test pieces is normal concrete (BN), palm shell ash concrete (BCS) with a percentage of 3%, 5%, and 7% plus silicafume 1.5% of the cement weight. The test specimen uses a cylinder with a diameter of 15 cm x 30 cm totaling 24 pieces. Based on the results of the maximum compressive strength of 7-day concrete life of 22.552 MPa of BN test piece, the minimum value is 19.155 MPa of 7% BCS test piece. At 28 days of concrete age, the maximum compressive strength is 26.893 MPa for 3% BCS test piece, and the minimum value is 22.364 MPa for 5% BCS test piece. Based on the results of the tests and analyses carried out, it can be concluded that the expansion of palm shell fiery remains and silicafume to the concrete blend can increment the compressive quality of concrete on average above 20 MPa over time due to the influence of the percentage of pozzolan shell ash and the addictive substance silicafume.